Impressive epoxy toughening by a structure-engineered core/shell polymer nanoparticle. (20th October 2020) - Ning, Na; Liu, Wanshuang; Hu, Qiaole; Zhang, Liying; Jiang, Qiuran; Qiu, Yiping; Wei, Yi
Abstract: Five polymer nanoparticles with different compositions and morphologies are prepared from methyl methacrylate, butyl acrylate and ethylene glycol dimethacrylate via aqueous emulsion polymerization. All the nanoparticles keep a discrete dispersion state when transferred into epoxy resin using a phase-transfer method. The addition of these nanoparticles almost has no impact on the cure and glass transition temperature of matrix resin. However, the results of mechanical tests demonstrate a clear correlation between nanoparticle structures and their effectiveness on toughening epoxy resins. Particularly, a soft core/rigid shell nanoparticle (B/M), represented by a 50/50 polybutyl acrylate core with a polymethyl methacrylate shell, shows an impressive toughening effect on the epoxy matrix. The addition of 10 wt% B/M gives 220% and 851% enhancement in critical stress intensity factor ( K IC ) and the critical strain energy release rate ( G IC ), respectively. Stress-induced whitening and cold drawing observed during tensile straining confirm the significant enhancement in fracture toughness. The microscopy observations show evidences of plastic void growth followed by the formation of plastic deformation, yielding and crazing, which absorb a significant amount of energy and inhibit crack propagation. Graphical abstract: Image 1